A magneto-optical study of bismuth-doped MgO – Al2O3 – SiO2 glass: on the nature of near-infrared luminescence *Presented at the 7th Russian Workshop on Fibre Lasers, Novosibirsk, 5–9 September 2016. (March 2017) - Laguta, A.V.; Denker, B.I.; Sverchkov, S.E.; Razdobreev, I.M.
Abstract: This paper presents results of a detailed magneto-optical spectroscopy study of bismuth-doped aluminosilicate glass. At least three distinct optical centres are shown to coexist in the glass: bismuth ion clusters, Bi + ions and defects in the glass structure, with energy transfer between the last two species. Analysis of magnetic circular dichroism and magnetic circular polarisation of luminescence as functions of magnetic field and temperature indicates that all three centres have an even number of electrons (holes). Experimental evidence is presented that both 'red' and near-infrared luminescence bands are due to transitions in the defects.